2002
DOI: 10.1078/0176-1617-0670
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of apricot plants grafted on two different rootstocks to flooding conditions

Abstract: SummaryThe effects of soil flooding on plant water relations and vegetative growth was studied in potted two-year-old apricot plants (Prunus armeniaca L., cv. Búlida) grafted on two different rootstocks: Pollizo prune (P. insititia L.) (P) and Real Fino apricot (RF). Plants were submitted outdoors to three treatments: T0, not flooded (control), and two flooded treatments for 3 (T1) and 6 (T2) days.Apricot water relations were seen to be adversely affected from first day of the flooding onwards. These effects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 24 publications
2
32
1
3
Order By: Relevance
“…D.A. Webb × Prunus persica [L.] Batsch) (Martinazzo et al, 2011), apricot (P. armeniaca) (Domingo et al, 2002;Nicolás et al, 2005), peach (Insausti and Gorjón, 2013), in peach-almond interspecific crosses and Prunus cerasifera Ehrh. (Xiloyannis et al, 2002), and the peach-almond hybrids 'Felinem' and 'Garnem' rootstocks (Amador et al, 2012).…”
Section: Scion-rootstock Graft Incompatibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…D.A. Webb × Prunus persica [L.] Batsch) (Martinazzo et al, 2011), apricot (P. armeniaca) (Domingo et al, 2002;Nicolás et al, 2005), peach (Insausti and Gorjón, 2013), in peach-almond interspecific crosses and Prunus cerasifera Ehrh. (Xiloyannis et al, 2002), and the peach-almond hybrids 'Felinem' and 'Garnem' rootstocks (Amador et al, 2012).…”
Section: Scion-rootstock Graft Incompatibilitymentioning
confidence: 99%
“…Subsequently, in Prunus, by prolonging the time of flooding many physiological anomalies can be observed or detected, the most common being lower chlorophyll content and less development (Amador et al, 2012;Insausti and Gorjón, 2013), increased defoliation (Ranney, 1994;Jacobs and Johnson, 1996), lower weight and root necrosis (Jacobs and Johnson, 1996), lower leaf water potential (Domingo et al, 2002;Nicolás et al, 2005;Insausti and Gorjón, 2013), less sap flow (Domingo et al, 2002;Nicolás et al, 2005), reduced turgor and leaf epinasty (Domingo et al, 2002), redness, and subsequent necrosis of leaf senescence and damage on vascular bundles (Iacona et al, 2013), all as symptoms of medium and long term appearance. In flooded peach (highly sensitive species) Insausti and Gorjón (2013) observed that fruit size was smaller and that harvested fruits produced ethylene earlier, advancing the climacteric ripening and softening of the fruit, seriously affecting fruit production.…”
Section: Scion-rootstock Graft Incompatibilitymentioning
confidence: 99%
“…Flooding can also cause a decline in the growth of petioles and leaf stomatal conductance (Domingo et al, 2002). Moreover, the saturation of the soil (i) interfere in the allocation of photoassimilates in woody and herbaceous plants, root can decrease metabolism and oxygen demand (Chen et al, 2002); (ii) inhibits the initiation of flower buds and the increase in fruit species not tolerant to flooding; (iii) induces abscission of flowers and fruits; (iv) reduces the quality of fruits due to the reduction of size, changing its appearance and interfering in its chemical composition (Kozlowski, 1997).…”
Section: Flooding Stressmentioning
confidence: 99%
“…The decrease of macronutrients and decrease of nutrients found in the leaves of plants not tolerant to flooding can be attributed to mortality of roots, decrease of mycorrhizae, root metabolism, transpiration and water conductivity (Domingo et al, 2002). The mechanisms presented by plants tolerant to water stress over which survive periods of flooding are complex (Pezeshki, 2001).…”
Section: Flooding Stressmentioning
confidence: 99%
“…이와 같은 환경 스트레스 요인들 하에서 증 산은 그 식물체가 반응하는 최초의 신호이며 (Christmann et al, 2007;Jia et al, 2002), 가뭄이나 침수와 같은 요인들의 반 응에 있어 조직의 수화 상태의 중요성이 연구들을 통해 잘 입증 되었다 (Aroca et al, 2001;Bouchabke-Coussa et al, 2008;Matsuo et al, 2009). 역설적이지만 홍수가 잎 건조에 영향을 미친다는 연구 결과들도 있다 (Domingo et al, 2002;Nicolás et al, 2005;Ruiz-Sánchez et al, 1996). 6.7 ± 6.7 ab 0 ± 0e Hohoba oil 40 ± 6.7 ab 13.3 ± 6.7de 0 ± 0d Linseed oil 26 ± 3.8ab 0 ± 0e Macadamia oil 6.7 ± 3.3 ab 0 ± 0e Olive oil 6.7 ± 6.7 ab 0 ± 0e Soybean oil 47.3 ± 10.4 ab 66.7 ± 8.8a 33.3 ± 8.8abc 6.7 ± 6.7a Potassium bicarbonate 26 ± 3.8 ab 0 ± 0e Sodium bicarbonate 16.7 ± 16.7 ab 3.3 ± 3.3e 0 ± 0d Sodium benzoate 6.7 ± 6.7 ab 0 ± 0e Dongbucover 13.3 ± 13.3ab 0 ± 0e Lemitrone 6.7 ± 6.7ab 0 ± 0e Newosmak 24.3 ± 12.3ab 0 ± 0e Sylluett 0 ± 0b 0 ± 0e LE9 6.7 ± 6.7 ab 0 ± 0e Tween 80…”
unclassified